Mediating effect of uncertainty on the relationship between interpersonal attraction traits and life happiness amongst Facebook users - Bolong, Jusang; Attan, Sri Azra (Human Resource Management Academic Research Society, 2020)
There is a large amount of uncertainty that needs to be assured for experiencing happiness in life since interpersonal attraction judgments are promptly developed during initial interactions. Thus, the objective of this study was to examine the mediating effect of uncertainty on the relationship between interpersonal attraction traits and life happiness amongst Facebook users. This study was using an integrated purposive sampling method through a snowballing procedure by considering the characteristics of respondents to suit the purpose of the study. A total of 503 questionnaires were distributed online, with only 402 respondents returned the questionnaire. It is found that there is a mediating effect of uncertainty on the relationship between interpersonal attraction traits and life happiness amongst Facebook users, namely physical attraction, social attraction, and extraversion. This study proposes the combination of the analytical unit for interpersonal attraction traits and life happiness by integrating the variable measurements in multiple contexts of social media platforms.